2000
DOI: 10.1212/wnl.54.9.1805
|View full text |Cite
|
Sign up to set email alerts
|

Poststroke depression and emotional incontinence

Abstract: Development of PSD and PSEI is strongly influenced by lesion location, probably associated with the chemical neuroanatomy related to the frontal/temporal lobe-basal ganglia-ventral brainstem circuitry. Although the lesion distribution is similar, PSEI is more closely related to lenticulocapsular strokes than is PSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
175
4
23

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(205 citation statements)
references
References 34 publications
3
175
4
23
Order By: Relevance
“…Most research has focused on biological explanations with an association between emotional lability and frontal lesions found in four cohorts 36,[41][42][43] and an association with dorsal lesions in the other. 44 A Cochrane review of pharmacological interventions to treat emotional lability after stroke (seven trials, 739 people, recruited at 6 days to 13 years after stroke) reported that antidepressants reduced its frequency and severity but confidence intervals were wide (figure 2).…”
Section: Emotional Labilitymentioning
confidence: 99%
“…Most research has focused on biological explanations with an association between emotional lability and frontal lesions found in four cohorts 36,[41][42][43] and an association with dorsal lesions in the other. 44 A Cochrane review of pharmacological interventions to treat emotional lability after stroke (seven trials, 739 people, recruited at 6 days to 13 years after stroke) reported that antidepressants reduced its frequency and severity but confidence intervals were wide (figure 2).…”
Section: Emotional Labilitymentioning
confidence: 99%
“…administered a structured questionnaire to patients and their relatives to establish the diagnosis of PSEI according to criteria of Kim and Choi-Kwon. 6 PSEI was considered present if patients showed excessive or inappropriate laughing, crying, or both compared with their premorbid state. If both the patient and cohabitating relative(s) agreed that excessive or inappropriate laughing or crying occurred on 2 or more occasions since the latest stroke, the diagnosis of PSEI was established.…”
Section: Diagnosis Of Pseimentioning
confidence: 99%
“…5 HRQOL has been used as an outcome measure in stroke research. 5 Determinants of stroke survivors' HRQOL include age, sex, 6 poststroke depression and anxiety, and physical function. 7 As a common poststroke complication, PSEI also may influence HRQOL adversely.…”
mentioning
confidence: 99%
“…10 Afflicted individuals are often disinhibited or unable to control their emotional expressivity, and there is a disconnection between external stimuli and the emotional responses. 10,22,23 These reactions (which cause distress, embarrassment, and avoidance of social situations and have been linked to depression) 6,10,18,20 often occur in the first weeks after the stroke and are acute, short-lived, and intense. 2,11,20,24 These features differentiate them from other psychological reactions (e.g., anxiety and depression) that can become chronic.…”
Section: What Are the Psychological Reactions To Stroke And When Do Tmentioning
confidence: 99%
“…11 Although pseudobulbar affect has not been linked to the level of ADLs, it has been found to be more prevalent in individuals with severe motor dysfunction (weakness of the limbs) and in those who have suffered an ischemic stroke (as opposed to a hemorrhagic stroke). 22 Premorbid factors. Certain premorbid conditions may increase the risk of psychological reactions to stroke.…”
Section: Which Patients Are More Likely To Develop Adverse Psychologimentioning
confidence: 99%